2010
DOI: 10.1111/j.1365-2923.2010.03725.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress-related factors on mental health status among resident doctors in Japan

Abstract: Residents' mental health was associated not only with working conditions, but also with their attitudes towards those working conditions. Enhancing residents' sense of 'reward from work' might be important in reducing their reactions to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 21 publications
5
61
0
Order By: Relevance
“…Perspective" (Rabin, Matalon, Maoz, & Shiber, 2005), and the other article investigated how the interaction between the ability of medical residents to cope with stress and their work might affect their level of job-related stress (Haoka, Sasahara, Tomotsune, Yoshino, Maeno, & Matsuzaki, 2010). Both articles focused highly on sense of coherence, and the second article used Antonovsky's sense of coherence questionnaire in their study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perspective" (Rabin, Matalon, Maoz, & Shiber, 2005), and the other article investigated how the interaction between the ability of medical residents to cope with stress and their work might affect their level of job-related stress (Haoka, Sasahara, Tomotsune, Yoshino, Maeno, & Matsuzaki, 2010). Both articles focused highly on sense of coherence, and the second article used Antonovsky's sense of coherence questionnaire in their study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data were gathered by means of an anonymous questionnaire distributed among the participants during identify specific stressful life experiences, though several respondents commented on the relationships with both other professionals as well as patients as a major source of stress. In the case of chronic stress, leading to underperformance [40], high satisfaction with career support, high sense of coherence [34,41], occupational self-efficacy [34], and low values regarding being overcommitted to ones work [35] seem to act as protective factors.…”
Section: Participantsmentioning
confidence: 99%
“…Antonovsky uses a concept called "sense of coherence" (SOC) to explain individual factors related to life stresses and health. SOC is defined as "a global orientation that expresses the extent to which one has a pervasive, enduring, though dynamic, feeling of confidence that one's internal and external environments are predictable and that there is a high probability that things will work out as well as can reasonably be expected" (Antonovsky & Sagy, 1986 Haoka et al (2010) reported that workload, mental workload, and problems in personal relationships that are perceived as job stressors are negatively associated with residents' psychological well-being, and reward from work is a buffer factor that is positively associated psychological wellbeing. However, this study was conducted just after the beginning of training and the number of participants was small.…”
Section: Introductionmentioning
confidence: 99%